Memories of my father - Belaunde Moreyra, José (Mercurio Peruano, 2018)
The author offers a reflection on the theme of faith in Víctor Andrés Belaunde, which is one of the main aspects, if not the most outstanding, of his personality and activity, without which his life and work would be inexplicable. He includes in the semblance personal memories and a consideration on the relevance of education.